Handbook of Active Marine Natural Products. - Zhou, Jiaju (De Gruyter reference ;, 2019)
This 8-volume set provides a systematic description on 8,350 active marine natural products from 3,025 various kinds of marine organisms. The diversity of structures, biological resources and pharmacological activities are discussed in detail. Molecular structural classification system with 264 structural types are developed. The 6th volume illustrates the molecular formula and structures of aliphatic metabolites.